Breastfeeding education and training for hospital-based nurses and midwives: a scoping review protocol of global evidence - Yong-Chuan Chen; Ya-Huei Chen (BMJ Open)
Introduction Hospital-based nurses and midwives play a pivotal role in promoting, protecting and supporting breastfeeding. However, variation in preservice education, in-service training and institutional policies contributes to inconsistent breastfeeding support across healthcare systems. Given the global push toward improving breastfeeding outcomes and the centrality of skilled nursing support, this scoping review protocol aims to systematically map the breadth, characteristics and reported outcomes of breastfeeding education and training initiatives targeting hospital-based nurses and midwives.Methods and analysis This scoping review will be conducted in accordance with the methodological framework developed by Arksey and O’Malley and advanced by the Joanna Briggs Institute (JBI). A systematic search will be conducted across major databases including OVID Medline, CINAHL, Scopus and Web of Science, as well as grey literature sources. Studies will be selected using the Population–Concept–Context (PCC) framework, focusing on breastfeeding-related education and training interventions designed for nurses and midwives in hospital settings. Two independent reviewers will screen all titles, abstracts and full texts, extract data using a standardised tool and resolve discrepancies via discussion or third-party consultation. The extracted data will be analysed using descriptive statistics and thematic synthesis to identify trends, gaps and directions for future research. The literature search will be conducted between August and October 2025.Ethics and dissemination This scoping review involves the analysis of existing literature and does not require ethical approval. The findings will be reported in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews (PRISMA-ScR) guidelines. Results will be disseminated through peer-reviewed publication and presentations at nursing and maternal–child health conferences to inform educators, hospital administrators and policy makers involved in breastfeeding support and clinical education.